SIFAT-SIFAT FUNGSI KONVEKS DAN QUASIKONVEKS PADA RUANG EUCLID BERDIMENSI HINGGA - Andryana Juanda, - (2020)
Convex and quasiconvex function had been studied by A. Robert Wayne and Dale E. Varberg, in fact the analogy of properties of convex and quasiconvex function was made. In this study will be researched and looked for new properties of convex and quasiconvex functions and compare it. One of our the result is that quasiconvex functions if and only if can be represented as monotonous functions either or at most as decomposition of two monotonous functions.